ChemInform Abstract: Atom‐Economic Route to Densely Functionalized Thiophenes via Base‐Catalyzed Rearrangement of 5‐Propargyl‐2H‐thiopyran‐4(3H)‐ones. Issue 49 (December 2015) - Tang, Chunlin; Qin, Jian; Li, Xingqi
Abstract: This novel reaction procedure involves a tandem retro‐thio Michael addition, a propargyl isomerization and an intramolecular thio‐addition to allenes (I).